Evaluation of the SST-SAS model for prediction of separated flow inside turbine internal cooling passages - Zacharzewski, Piotr; Simmons, Kathy; Jefferson-Loveday, Richard; Capone, Luigi (2016)
The flow and heat transfer over a three-dimensional axisym-metric hill and rectangular ribbed duct is computed in order to evaluate the Shear Stress Transport - Scale Adaptive Simulation (SST-SAS) turbulence model. The study presented here is rele¬vant to turbine blade internal cooling passages and the aim is to establish whether SAS-SST is a viable alternative to other turbulence models for computations of such flows. The model investigated is based on Menter‘s modification to Rotta‘s k-kL model and comparison is made against experimental data as well as other models including some with scale resolving capability, such as LES, DES & hybrid LES-RANS. For the hill case the SAS model dramatically overpredicts the size of the separation bubble. The LES on the other hand proved to be more accurate even though the mesh is courser by LES standards. There is little improvement of SST-SAS compared with RANS. Broadly speaking all models predict streamwise ve¬locity profiles for the ribbed channel with reasonable accuracy. The cross-stream velocity is underpredicted by all models. Heat transfer prediction is more accurately predicted by LES than RANS, DES & SST-SAS on a mesh that is slightly coarser than required by LES standard, however it still exhibits significant er¬ror. It is concluded that more investigation of the SST-SAS model is required to more broadly assess its viability for industrial com¬putation.